Building Sustainable Education with the Literacy and Research-oriented Cooperative Problem-based Learning: A Bridge in the Activeness of Chemistry Education Students - Pratama, Faiz Ilham; Rohaeti, Eli; Laksono, Endang Widjajanti (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to examine the effect of the LIRACLE model (Literacy and Research-Oriented Cooperative Problem-Based Learning) on student activeness in undergraduate chemistry learning. LIRACLE is an innovative instructional model that integrates literacy strategies, cooperative learning, and research-based approaches within a problem-based learning framework. The study employed a quasi-experimental design with two groups: an experimental group (38 students) that received the LIRACLE treatment and a control group (44 students) that followed conventional PBL. Student activeness data were collected through observation sheets over six class meetings and analyzed using the Mann-Whitney test due to the non-normal distribution of the data. The results showed a significant difference in student activeness between the experimental and control groups, with a significance value of 0.000 (p < 0.05). Students who participated in LIRACLE-based learning demonstrated higher levels of engagement, both cognitively, socially, and affectively. The implementation of LIRACLE proved effective in creating a participatory and reflective learning environment, encouraging students to take an active role in constructing their understanding. These findings support the importance of developing active learning strategies in higher education, particularly to achieve meaningful chemistry learning outcomes in alignment with Sustainable Development Goal 4.